U.S.-Singapore Commodity Trade and the J-Curve - Bahmani-Oskooee, Mohsen; Harvey, Hanafiah (Asian Economic and Financial Review, 2014)
Limited number of studies that investigated the short-run (J-Curve) and long-run effects of currency depreciation on the trade balance of Singapore either used aggregate trade data between Singapore and rest of the world or between Singapore and her major trading partners. While they were able to provide some evidence supporting short-run effects (not following the J-curve), they were unable to discover any long-run effects, especially in the trade between Singapore and the U.S. In this paper we add to the literature by disaggregating the Singapore-U.S. trade flows by commodity and consider the trade flows of 64 industries that trade between the two countries. We find short-run significant effects in 48 industries. The short-run effects last into the long run only in 24 industries. Combining the old and new definition of the J-curve, we support the concept in 27 industries.